MATERNAL STRESS AND NEWBORN BEHAVIOR, MATERNAL DEPRESSION AND NEWBORN COGNITION - LASHARI, K; KUMARI, M; SHAHKAR, SM; FAROOQUI, A; SANGEET, .; ZAFAR, MS (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study is to determine the relationship between maternal stress, maternal depression, and newborn behavior/cognition. This cross-sectional study included 60 participants and their newborn babies. Maternal depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS), while the Perceived Stress Scale (PSS-10) was used to measure stress levels. The newborn behavior/cognition was measured using the BSID-III Screening Test scores. Data was collected from January 2023 to June 2023. Mothers had an average age of 35.63± 7.22 years, while the newborn infants had an average of 8.61± 3.27 years. Among the newborns, 56.7% were male infants, while 43.3% were female infants. The study determined the characteristics of enrolled patients and their newborn infants. The correlations between BSID-III Screening Test scores and maternal depression, as well as maternal stress, were also presented. The study showed that there was a correlation between cognitive development and maternal depression, with an R-value of 0.19 and an insignificant P-value of 0.14. Similarly, a correlation was found between cognitive development and maternal stress, with an R-value of 0.17 and an insignificant P-value of 0.17. The study concluded that maternal stress during pregnancy can impact newborn behavior, highlighting the importance of addressing maternal stress and depression, not only for the well-being of the mothers but also for fostering healthy newborn behavior and cognitive development.